2001
DOI: 10.1007/s002130000638
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting of money and alcohol in actively using alcoholics, currently abstinent alcoholics, and controls

Abstract: These data provide further evidence of more rapid discounting of delayed rewards in alcohol abusers compared to controls, and especially steep discounting among current users. Rapid discounting of delayed rewards may be a feature related to addictive disorders. A better understanding of how delaying rewards in time impacts their value may have implications for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
529
4
17

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 683 publications
(597 citation statements)
references
References 51 publications
(67 reference statements)
47
529
4
17
Order By: Relevance
“…Consistent with previous findings (Vuchinich and Simpson, 1998;Petry, 2001;Mitchell et al, 2005b), the AA group made impulsive choices significantly more often than the CS group (F 1,16 ¼ 5.846, p ¼ 0.028). Also, consistent with our previous findings (Mitchell et al, 2005b), ICR was sensitive to both the later reward delay (Figure 2c; F 1.74,27.83 ¼ 12.35; po0.001) and the later reward amount (Figure 2d; F Figure 2d).…”
Section: Acute Ntx Does Not Reduce Impulsive Choice In Either Groupsupporting
confidence: 91%
“…Consistent with previous findings (Vuchinich and Simpson, 1998;Petry, 2001;Mitchell et al, 2005b), the AA group made impulsive choices significantly more often than the CS group (F 1,16 ¼ 5.846, p ¼ 0.028). Also, consistent with our previous findings (Mitchell et al, 2005b), ICR was sensitive to both the later reward delay (Figure 2c; F 1.74,27.83 ¼ 12.35; po0.001) and the later reward amount (Figure 2d; F Figure 2d).…”
Section: Acute Ntx Does Not Reduce Impulsive Choice In Either Groupsupporting
confidence: 91%
“…(1999) showed that substance abusers discounted delayed outcomes at greater rates than non-abusers. Similar findings have been reported with abusers of nicotine (Bickel et al, 1999), opioids (Madden et al, 1997), and alcohol (Petry, 2001;Vuchinich and Simpson, 1998). Despite the fact that a correlation between drug abuse (and other behaviors often characterized as impulsive) and delay discounting has been demonstrated, it is not clear whether increased delay discounting underlies drug abuse and other disorders or if long-term exposure to drugs or other variables underlie increased delay discounting.…”
Section: Introductionsupporting
confidence: 58%
“…Although it may not be meaningful to ask how steeply individuals without addiction discount heroin, it is possible to determine how steeply individuals without alcoholism discount alcohol. Petry's (2001a) study addressed this interesting issue. She found that although nonalcoholics discounted both hypothetical money and alcohol less steeply than alcoholics, alcoholics and nonalcoholics both discounted alcohol more steeply than money.…”
Section: Applications To Group Differencesmentioning
confidence: 99%